A quasi-reagentless point-of-care test for nitrite and unaffected by oxygen and cyanide - Monteiro, Tiago (2019)
This work was supported by the Applied Molecular Biosciences Unit-UCIBIO which is financed by national funds from FCT/MCTES (UID/Multi/04378/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728). C.M.S. and T.M. thank the financial support from Fundacao para a Ciencia e Tecnologia (Fellowships SFRH/BPD/79566/2011 and PD/BD/109687/2015).